Gaya Bahasa dalam Geguritan "Mung Sliramu" Karya Bambang Sulanjari - Mulyanti, Lisa Dewi; Alfiah, Alfiah (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
The purpose of this study was to analyze the language style contained in the geguritan "Mung Sliramu" by Bambang Sulanjari. This research uses qualitative research, which is research that produces descriptive data in the form of written words. The approach used in the research of Language Style in Geguritan "Mung Sliramu" by Bambang Sulanjari uses a stylistic approach. The data used in this study is descriptive data in the form of phrases, words, and sentences. The primary data source of the study was the geguritan "Mung Sliramu" by Bambang Sulanjari. By using secondary data sources in the form of articles, documents, books that lead to stylistic studies. This analysis technique uses descriptive analysis, done by describing the style of language in Bambang Sulanjari's Mung Sliramu geguritan. Data collection techniques with read and record techniques. The results of this study showed that in the guritan "Mung Sliramu" by Bambang Sulanjari found some stylistic usage; (1) linkage language style, (2) comparative language style, (3) purwakanthi guru swara, and (4) purwakanthi basa.